Hyperplastic processes of the endometrium in premenopausal women: modern opportunities of hormonal correction and prevention - L V Tkachenko; N I Sviridova (IP Berlin A.V., 2013)
Hormonal therapy prescribed for endometrium hyperplastic processes is essentially for preventive treatment aimed at correcting the menstrual cycle, reducing apparent estrogenic effects and preventing the formation of endometrial hyperplasia. Currently, the arsenal of physicians have a wide range of products for the treatment of endometrial hyperplastic processes. These include progestins, combined oral contraceptives (COC), antigonadotropic drugs and gonadoliberin agonists. We carried out a clinico-morphological evaluation of the effectiveness of COCs Mediana for the prevention of recurrent endometrial hyperplastic processes in patients with associated cardiovascular disease in premenopausal women.